The journey of human life and the grandeur of nature: Art-based research on the creation of batik inspired by cultural visual icons of Cirebon and Japan - Mahadewi, Kirana; Wulandari, Dwi (Universitas Negeri Yogyakarta, 2024)
This research aims to (1) develop a concept for pattern creation, (2) describe the process, (3) describe the results, and (4) reflect on the researcher's experience in creating batik patterns combining visual icons from Cirebon and Japan. The research method used is art-based research, including the stages of exploration, design, and realisation. Data was collected through literature studies and documentation to identify ideas, concepts, techniques, and styles. The research results show: (1) The pattern has the concept of the human life journey and the greatness of nature through the exploration of the characteristics of Batik Mega Mendung, Cirebon Masks, The Great Wave off Kanagawa painting, and Geisha. (2) The creation uses Indonesian batik techniques, starting from the preparation of tools and materials, application of sketches, canting, colouring, and removing the wax. (3) This research produced five patterns of painted batik titled